Realitas Perkembangan Investasi Asing Langsung di Indonesia Tahun 2019 - Mahadiansar; Ramadhani Setiawan; Eki Darmawan; Fitri Kurnianingsih (Research and Development Agency Ministry of Home Affairs, 2021)
Foreign direct investment in Indonesia has a very significant impact on the progress of a developing country to improve the welfare of the people. This research focuses on the conditions that occur in foreign direct investment in Indonesia in 2019 with various existing problems. The method used was by reviewing studies advanced in literature. The results show that there needs to be an independent body that controls or supervises the course of foreign direct investment, especially in areas that have the potential to invest, a very strong alternative in this paper needs to involve local governments in special economic zones (KEK) so that foreign direct investment can be felt in the region which has the potential to be empowered both in the use of natural and human resources.